Output Volatility and Large Output Drops in Emerging Market and Developing Countries - Hakura, Dalia (IMF Working Papers; Working Paper, 2007)
This paper establishes that output volatility and the size of output drops have declined across all countries over the past three decades, but remain considerably higher in developing countries than in industrial countries. The paper employs a Bayesian latent dynamic factor model to decompose output growth into global, regional, and country-specific components. The favorable trends in output volatility and large output drops in developing countries are found to result from lower country-specific volatility and more benign country-specific events. Evidence from cross-section regressions over the 1970-2003 period suggest that discretionary fiscal spending volatility, and terms of trade volatility together with exchange rate flexibility are key determinants of volatility and large output drops.